ASSISTANCE IN CONSTRUCTING SEMIOTIC AND PHILOSOPHICAL MEANING MASCOT “KUCING CONDROMOWO” MOJOKERTO CITY AT THE 2023 EAST JAVA PROVINCIAL SPORTS WEEK - Ramadhani , Rakhmad Saiful; Ningsih, Masnia (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2025)
Assistance in constructing the "Kucing Condromowo" mascot for the 2023 East Java Provincial Sports Week (PORPROV) in Mojokerto City integrates local historical, cultural, and semiotic values. The selection process employed the concept of "Endemic Spirit," emphasizing native animals and cultural symbols representative of the region's identity. The cat, rooted in historical and cultural significance, was chosen for its agility, a trait reflecting athletic excellence. The name "Kucing Condromowo" embodies the philosophical and historical narrative of Mojokerto's traditions. The mascot design incorporates elements such as Iket Sambang blangkon, symbolizing self-control and remembrance, and the Surya Mojopahit necklace, which reflects Mojokerto’s historical ties to the Majapahit Kingdom. Additional design features like the patterned Sulur Gringsing cloth and color symbolism of the "telon" cat (white, yellow, red, and black) convey values of purity, ambition, resilience, and balance. This mascot transcends its role as an event symbol to serve as an emblem of regional pride and identity, aligning with PORPROV’s mission to celebrate sportsmanship and promote local culture. The initiative also emphasizes preserving Mojokerto’s traditional crafts and introducing them to future generations.